Evaluation of Bronchiolar and Alveolar Cell Injuries Induced by Short- and Long-term Exposure to Sidestream Smoke - Kwon, Kun-Young (The Korean Society of Pathologists and The Korean Society for Cytopathology, 2012)
BACKGROUND: We investigated effects of short- and long-term exposure to sidestream smoke on the bronchiolar and alveolar cells in Sprague-Dawley rats. METHODS: Rats were divided into five experimental groups: groups 1, 2, and 3 (1-month exposure to 3, 5, and 7 cigarettes a day, respectively), groups 4 and 5 (3- and 6 month exposure to five cigarettes a day, respectively). We examined the morphologic changes, the expressions of tumor necrosis factor α (TNF-α), tumor growth factor β1 (TGF-β1), interlekin (IL)-1α, IL-1β, Ki-67, and cytokeratin 14 and in situ apoptosis in the bronchiolar and alveolar cells on light microscopy (LM) and electron microscopic (EM) terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) staining. RESULTS: LM showed the respiratory bronchiolar dilatation and alveolar wall collapse. In groups 3, 4, and 5, EM showed loss of the cilia and Clara cells with irregular size, more prominent alveolar wall collapse and dilation of alveolar duct than those of groups 1 and 2. Bronchiolar and alveolar cells showed increased expressions of TNF-α and TGF-β in groups 4 and 5. LM and EM TUNEL stains showed increased apoptosis in groups 3, 4, and 5. CONCLUSIONS: Sidestream smoke causes a bronchiolar and alveolar cell injury and the severity correlates strongly the volume and duration of exposure to sidestream smoke.